Prevention of peptic ulcer by aqueous extract of Aegle marmelos leaf in rats - Rahman, Sharmin; Quader, Mohammad Rezaul; Khan, Md Ismail (IMC Journal of Medical Science, 2018)
Background and objectives: Aegle marmelos (Bael), a medicinal plant, has been widely used indigenously to treat many diseases in Bangladesh and other countries. The present study was carried out to evaluate the efficacy of A. marmelos leaf to prevent ethanol induced gastric ulcer in a rat model. Methods: Thirty two Wister albino rats of either sex, weighing between 100-150g, were fed 200 mg/kg or 400 mg/kg aqueous extract of A. marmelos leaves one hour prior to oral administration of 90% ethanol (1 ml/200 gm body weight) to induce gastric ulcer. The animals were sacrificed after one hour and ulcer scores and index were determined. The protective efficacy of A. marmelos aqueous extract was expressed as percentage protection of ulcer. Results: Aqueous extract exhibited significant (p<0.05) dose dependent protection against gastric ulcer formation by ethanol in rat stomach. Percentage protection of ulcer with 200 mg/kg and 400 mg/kg of aqueous extract of A. marmelos leave were 19.3% and 37.2% respectively compared to standard anti-peptic ulcer drug omeprazole (50.4%). Conclusion: Thus, crude extracts of A. marmelos leave have been shown to have potential ability to prevent experimentally induced peptic ulcer formation in animal model. IMC J Med Sci 2018; 12(1): 11-14